Factor influencing the act of whistleblowing in an organization / Siti Khalijah Said - Said, Siti Khalijah (2014)
This research is conducted to examine the relationship between attitudes towards whistleblowing, internal control and commitment with the act of whistleblowing in the organization besides to determine the most factor that contribute to the act of whistleblowing in the organization. This research was conducted at Penang Port Sdn Bhd. The methodology used by the researcher consists of research design, population and sampling, data collection method and data analysis method. The questionnaire was distributed among employee of Penang Port Sdn Bhd where the number of respondent contributed was 117 respondents. The data gathered was being analyzed by using Statistical Package for Social Science (SPSS) version 20. Finding shows that the entire factors are positively associated to the act of whistleblowing. The result shows out of three factors, only two factors have a significant relationship toward act of whistleblowing which are attitudes toward whistleblowing and internal control. Alternate hypotheses (H1) are accepted for the hypotheses 1 and hypotheses 2 while for hypotheses 3 is rejected. The implication of findings to the organization is discussed besides offer the direction for future research.